2018
DOI: 10.1038/s41419-017-0194-1
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with proteasome inhibitors and TLR agonists enhances tumour cell death and IL-1β production

Abstract: Proteasome inhibitors have emerged as an effective therapy for the treatment of haematological malignancies; however, their efficacy can be limited by the development of tumour resistance mechanisms. Novel combination strategies including the addition of TLR adjuvants to increase cell death and augment immune responses may help enhance their effectiveness. Although generally thought to inhibit inflammatory responses and NF-κB activation, we found that under specific conditions proteasome inhibitors can promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Specifically, the increased activity of the TLR signaling pathway has been associated with hematopoietic and AML differentiation 36 , 37 . Activating TLRs using agonists represents a promising avenue for cancer immunotherapy and there is accumulating evidence supporting a potential role for such agonists in the treatment of AML 38 , 39 . The differential activity of the TLR pathway among the subtypes might present an opportunity for TLR agonist-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the increased activity of the TLR signaling pathway has been associated with hematopoietic and AML differentiation 36 , 37 . Activating TLRs using agonists represents a promising avenue for cancer immunotherapy and there is accumulating evidence supporting a potential role for such agonists in the treatment of AML 38 , 39 . The differential activity of the TLR pathway among the subtypes might present an opportunity for TLR agonist-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TNF-a is an inflammatory mediator and functions as an anti-tumorigenic factor at high concentrations (35). IL-1b is also reported to mediate anti-tumor responses through T lymphocytes (36,37). Our previous studies found that US31 interacted with NF-kB2 (22), leading to phosphorylated P100 polyubiquitination and activating NF-kB2 (22).…”
Section: Discussionmentioning
confidence: 98%
“…To identify whether apoptosed BM-DC cells were associated to caspase-3, BMDCs were pulsed with increased concentrations of rSIP for 12 h. Apoptosis of BM-DCs pulsed with rSIP was not associated to caspase-3 activation (Figure 4H). These results indicate that rSIP is nontoxic at concentrations below 0.1 µg/mL and that rSIP can be associated to BM-DC necroptosis, a form of cell death known to involve inflammasome activation and IL-1β secretion, which proceeds in a caspase-independent manner [15].…”
Section: Activation Induced Cell Death Upon Rsip Stimulationmentioning
confidence: 79%